Construction and Validation of a Knowledge Test on Pesticide Safety for Vegetable Growers - Prashish Singh; Kalyan Ghadei; Shubhadeep Roy; Jaydeep Halder; Jagriti Kumari; Gyan Shukla (Indian Journal of Extension Education, 2025)
Vegetable farmers frequently utilize a diverse array of pesticides at varying doses to mitigate yield losses arising from insect pests, pathogens, and other biotic stresses. Although pesticide use has substantially contributed to enhanced crop productivity, a growing body of scientific evidence highlights that indiscriminate, excessive, or unsafe pesticide use can impose serious health hazards on applicators and consumers, while also generating adverse ecological consequences. In this context, the present study was conducted in 2025,developed and standardized a comprehensive knowledge test to assess vegetable growers’ understanding of safety measures in pesticide application. An initial pool of 82 items was generated ensuring coverage of all critical dimensions of pesticide safety. Based on relevancy scores obtained from 60experts, 45 items were shortlisted for further evaluation. Item analysis was performed using three statistical indices: difficulty index, discrimination index, and point biserial correlation. Following established psychometric criteria, 38 items were retained with difficulty values between 30–70, discrimination indices ranging from 0.30–0.80, and a minimum point biserial correlation of 0.15. The finalized test comprised 38 items and demonstrated high internal consistency, with a Cronbach’s alpha coefficient of 0.90, confirming its reliability for assessing knowledge on pesticide safety.